From bias to exclusion: A multilevel emergent theory of gender segregation in organizations. Research in Organization Behavior, 32, 137-162. - Martell,Richard (Research in Organizational Behavior, 2012)
From bias to exclusion: A multilevel emergent theory of gender segregation in organizations 2012 Richard F. Martell | Cynthia G. Emrich | James Robison-Cox Abstract: This article presents a multilevel emergent theory of organizational segregation linking gender bias in performance assessment (a micro-level phenomenon) to gender segregation in organizations (a macro-level phenomenon). Based on an integration of multilevel research, emergence and signaling theory, we propose the following: (a) gender segregation in organizations is an emergent phenomenon that arises from the collective behavior of individuals who express only a small bias in favor of males, in concert with the signals governing promotion decisions and organizational mobility; (b) the emergence of a gender-segregated organization is often unintentional and the bottom–up and top–down processes that produce segregation are difficult to see; and (c) agent-based modeling is especially well-suited for illuminating the dynamics of bias that produce gender-segregated organizations. This multilevel emergent-based theory contributes to the research literature on organizational stratification by: (a) revealing the manner in which micro-level and macro-level forces conspire, oftentimes unwittingly, to produce gender-segregated organizations; (b) providing new and very different directions for future research on gender segregation that rely on agent-based modeling; and, most importantly, (c) moving a 30-year debate over the “real-world” impact of gender bias that continues to occupy the field of human resource management and, most recently, Supreme Court justices on to more fertile ground.
Keywords: Management